2023
DOI: 10.1111/iar.12486
|View full text |Cite
|
Sign up to set email alerts
|

Chronological and geochemical characteristics of metavolcanic rocks in the Nanping‐Ninghua tectonic belt: Constraints on the formation of the Cathaysia block

Abstract: The tectonic properties of the Nanping‐Ninghua tectonic belt (NNTB) play a crucial role in understanding the tectonic evolution of the Wuyi orogenic belt, which is related to the Neoproterozoic‐Paleozoic tectonic evolution of the Cathaysian Block. In this study, We present comprehensive petrological, geochronological, and geochemical data on the metavolcanic rocks from the Louqian Formation in Changting, Fujian Province. Our results show that volcanism in Changting occurred between 740.4 and 723.5 Ma, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Meanwhile, a suit of Early Paleozoic subduction accretionary rocks at Chencai area was identified, indicating that the ocean between the Yangtze and Cathaysia blocks was still present in the Paleozoic (Wang et al, 2016; Zhao et al, 2020; Zhu et al, 2023). Wen et al (2023) proposed that the Wuyi terrane was not unified in the Neoproterozoic and that the Cathaysia block was composed of multiple terranes before Early Paleozoic. All of these finding provide strong evidence for the early Paleozoic subduction‐accretionary collisional event along the Jiangshan‐Shaoxing fault.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a suit of Early Paleozoic subduction accretionary rocks at Chencai area was identified, indicating that the ocean between the Yangtze and Cathaysia blocks was still present in the Paleozoic (Wang et al, 2016; Zhao et al, 2020; Zhu et al, 2023). Wen et al (2023) proposed that the Wuyi terrane was not unified in the Neoproterozoic and that the Cathaysia block was composed of multiple terranes before Early Paleozoic. All of these finding provide strong evidence for the early Paleozoic subduction‐accretionary collisional event along the Jiangshan‐Shaoxing fault.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that,Zhao et al (2015) suggested that the Chencai Complex is the residual of early Paleozoic oceanic crust. Meanwhile, a suit of Early Paleozoic subduction accretionary rocks at Chencai area was identified, indicating that the ocean between the Yangtze and Cathaysia blocks was still present in the Paleozoic(Wang et al, 2016;Zhao et al, 2020;Zhu et al, 2023) Wen et al (2023). proposed that the Wuyi terrane was not unified in the Neoproterozoic and that the F I G U R E 1 1 Plot of Ca versus Fo contents in olivine form the TZF and FMT ultramafic intrusions (afterLi et al, 2012).F I G U R E1 2 Cartoon model illustrating the ultramafic-mafic magmas production induced by subducting Paleo-South Oceanic slab and ultramafic magma underplating at the root of continental arc.…”
mentioning
confidence: 99%
“…The Louqian formation (Z 2 lq), which mainly comprises the meta-volcanic rocks, has centralized ages ranging from 720 to 760 Ma (Table S1 and Figure et al, 1984), indicating that these rocks were forming in an active continental margin setting associated with subduction (Figure 14c,d;Schandl & Gorton, 2002). Some reports of the geochemical data of the meta-volcanic rocks in the Louqian formation (Z 2 lq) indicated these rocks formed in an island arc environment (e.g., Jiang et al, 2019;Liu et al, 2021;Wen et al, 2023), which are consistent with our research. The Wanquan group was suggested to be formed in active continental margin by previous research (Jiang et al, 2019;Jin, Zhang, Zhong, Zhou, Xiang, Zeng, & Li, 2008;Jin, Zhang, Zhong, Zhou, Xiang, Zeng, & Liu, 2008;Wei et al, 1997) terrane (Figure 13), which is geographically closer to the North Wuyi terrane.…”
Section: Samples Mx-22 From the Huangtan Formation (Pt 2-3 H) In The ...mentioning
confidence: 98%